Serum sodium within the normal range and its U-shaped relationship with biological aging in U.S. adults - Tong, Xianxiang; Wang, Fei; Liu, Mengxue (Frontiers in Nutrition, 2025)
BackgroundThis cross-sectional study evaluated the correlation between serum sodium levels (135–145 mmol/L) and biological aging in U.S. adults. Biological age, derived from multi-system biomarkers, provides a more accurate assessment of aging than chronological age. Hydration balance, reflected by serum sodium, may modulate age-related diseases and mortality, but its link to biological aging remains underexplored.MethodsUsing NHANES data (1999–2018), we focused on normonatremic adults (≥20 years). The final cohort included 18,301 participants. Biological age was estimated using the Klemera and Doubal method, and ∆age (biological age—chronological age) was calculated. Associations were assessed using multivariate regression, generalized additive models, and threshold analysis. Subgroup analyses were conducted for variations across different populations.ResultsNonlinear analysis revealed a U-shaped relationship between serum sodium and biological age. The lowest biological age occurred at 139.3 mmol/L: each 1 mmol/L increase below this threshold was associated with a reduction of 0.10 years in biological age (95% CI: −0.15, −0.05), whereas values above it showed a 0.08-year increase (95% CI: 0.04, 0.13). For ∆age, a negative association was observed below 141.2 mmol/L, with each increase linked to a 0.07-year decrease (95% CI: −0.10, −0.04). Subgroup analyses revealed significant interactions in diabetic and smoking populations.ConclusionMaintaining serum sodium levels within an optimal range (138–142 mmol/L) may help delay biological aging. Hydration management may serve as a modifiable factor for healthy aging, particularly in high-risk groups such as individuals with diabetes or tobacco use.